Expedito Vianna: um flautista à frente de seu tempo - Fernando Pacifico Homem (2005)
Expedito Vianna was an extremely active and influential flutist and teacher in Belo Horizonte, MG (Brazil) and Salvador, BA (Brazil) from the 1960's to the 1980's. Through pioneer research, he proposed methodologies for the study of the flute, that were before their time in Brazil. Some of his techniques, such as the use of phonemas, rhythmic dislocation, and transposition, once considered innovative, still serve as important tools for his former students in their professional lives today. Expedito Vianna was not only ahead of the Brazilian flutists of his generation, but his ideas were so ahead of his time that even today they remain current. Many flutists and teachers around the worfd today utilize similar techniques and pedagogic practices. Four of Vianna's main pedagogic techniques will be discussed in this study: altering sound quality through the use of vowels, solving difficult excerpts from the flute repertoire by re-grouping notes, the application of Marcel Moyse's sonority exercises for difficult flute passages, and tonal studies based on transposing melodies. Vianna's work will be compared with that of other present-day flutists and authors to show its validity within the broader spectrum of modem flute teaching. Vianna never concerned himself with seeking musical acclaim or stardom in the flute world. His ideas spread simply because they constitute effective educational tools. Several of his former students occupy important professional positions throughout Brazil today, which is the greatest proof of the effectiveness of his ideas.